Development of Augmented Reality Multiple Markers Application Used for Interactive Learning Media - Pratama, Alvonda Rizqi; Sukirman (Politeknik Ganesha Medan, 2023)
Augmented Reality (AR) is a technology that can turn virtual objects in the form of two dimensions (2D) or three dimensions (3D) into an object that looks real, then able to display objects in real-time. Using AR technology, you can visualize learning material into 3D objects to make it easier to understand when using it as a learning medium. This research aims to develop an AR application with multiple marker features that can be used as an interactive learning medium. The method used is Research and Development (R&D), and the development model used is 4D. The evaluation used was the Software Usability Measurement Inventory (SUMI), involving 11th-grade which involved 30 students consisting of 20 male students and 10 female students, the parameters assessed in this evaluation were between others are Efficiency, Affect, Helpfulness, Control, and Learnability. Based on the analysis performed on these parameters, the results show that all five parameters obtain valid and reliable results for each parameter in the validity and reliability tests with a Cronbach's alpha score of 0.934 (Efficiency), 0.868 (Affect), 0.917 (Helpfulness), 0.878 (Control), and 0.919 (Learnability). Thus, this multiple marker-based interactive learning media, Augmented Reality (AR), can be used in learning activities.